2009
DOI: 10.1002/jmri.21689
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast‐enhanced magnetic resonance imaging of abdominal solid organ and major vessel: Comparison of enhancement effect between Gd‐EOB‐DTPA and Gd‐DTPA

Abstract: Purpose:To evaluate the differences in enhancement of the abdominal solid organ and the major vessel on dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) obtained with gadolinium ethoxybenzyldiethylenetriamine pentaacetic acid (Gd-EOB-DTPA: EOB) and gadolinium diethylenetriamine pentaacetic acid (Gd-DTPA) in the same patients. Materials and Methods:A total of 13 healthy volunteers underwent repeat assessments of abdominal MR examinations with DCE-MRI using either Gd-DTPA at a dose of 0.1 mmol/kg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 22 publications
2
88
0
Order By: Relevance
“…When compared to Gd-BOPTA, at standard doses Gd-EOB-DTPA demonstrates lower enhancement in normal vasculature and solid abdominal organs [9] and lower dynamic enhancement of the liver vasculature [10]. Frydrychowicz et al compared dynamic post contrast hepatic vasculature signal to noise ratio (SNR) with the higher (non-FDA approved) Gd-EOB-DTPA dose of 0.05 mmol/kg to the standard dose of Gd-BOPTA.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to Gd-BOPTA, at standard doses Gd-EOB-DTPA demonstrates lower enhancement in normal vasculature and solid abdominal organs [9] and lower dynamic enhancement of the liver vasculature [10]. Frydrychowicz et al compared dynamic post contrast hepatic vasculature signal to noise ratio (SNR) with the higher (non-FDA approved) Gd-EOB-DTPA dose of 0.05 mmol/kg to the standard dose of Gd-BOPTA.…”
Section: Discussionmentioning
confidence: 99%
“…This is only a quarter of the dose of conventional extracellular contrast agents (0.1 mmol/ kg) [18,19]. The weight-adjusted contrast volume of gadoxetate disodium (concentration: 0.25mol) results in half the volume of other extracellular contrast agents (concentration: 0.5mol) [20].…”
Section: Influence Of Contrast Dosementioning
confidence: 99%
“…The smaller volume shortens the duration of arterial enhancement and reduces signal intensity [21]. Therefore, some institutions use higher doses of 0.05 mmol/kg [18,22,23]. Other institutions use a fixed dose of 10 ml equaling the package size, resulting in varying concentrations of gadoxetate disodium, depending on the patient's body weight [6, 8 -10, 12, 14].…”
Section: Influence Of Contrast Dosementioning
confidence: 99%
“…Contrast enhancement of the vessels is lower on the arterial phase for gadoxetic acid-enhanced images than for extracellular GBCAs. 9 The T 1 -shortening eŠect of gadoxetic acid is much larger than that of extracellular GBCAs, but that can result in equivalent or even greater contrast enhancements in the aorta. 10 A recent study revealed that use of a slow injection rate (one mL/s) can facilitate equivalent arterial enhancements between gadoxetic acid and extracellular GBCAs.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…64,65 Several studies have shown that gadoxetic acid-enhanced MR imaging is useful in diagnosing conventional HCCs and, in fact, may sometimes be more reliable than dynamic contrast-enhanced 16-to 64-slice multidetector-row CT for this purpose. 9,36,66,67 When using an extracellular GBCA, sensitivity and specicity of MR imaging are excellent even for small HCCs. 68 However, some researchers suggest that the hepatocyte phase of gadoxetic acid might have added value to detect more HCCs than dynamic phases especially for less-experienced observers.…”
Section: Added Value For Hepatocellular Carcinoma (Hcc) Improving Diamentioning
confidence: 99%